Artificial Intelligen Versus Manusia Dalam Sistem Informasi Modern - Sherina Rina; Muhammad Irwan Padli Nasution (Yayasan Salam Cerdas Al-Fattah, 2025)
AI has transformed the way companies manage data, make decisions, and conduct operations. Machine learning, predictive analytics, and natural language processing enable information systems to adapt automatically. AI can process large amounts of data quickly and accurately, create intelligent digital environments, and provide strategic recommendations for business decision-making. Through service automation, AI implementation also improves data security and user experience. However, issues such as ethics, data privacy, and dependency on technology remain key concerns. Overall, the digital transformation towards efficiency, innovation, and global competitiveness is driven by the use of AI in contemporary information systems.